Contributions (possible) of lacanian psychoanalysis to the non-essentialist feminist theorization - Delgado Ramos, Guillermo Enrique (2021)
With the aim of contributing to the theory of feminist emancipation policy, the work supports five confluences of Jacques Lacan's psychoanalyst's approaches to non-essentialist feminisms. For this, a review is carried out that systematizes the Lacanian developments in four theoretical waves, the same ones that are located in the critical tradition to the approaches on women proposed by Sigmund Freud, tradition exerted from feminism and from psychoanalysis. On this basis, and without ignoring the different discursive and political nature of Lacanian psychoanalysis and feminism, five contributions are proposed that constitute both starting points for a theorization to come: the relations between subject and emancipation, the objection to identity essentialisms, criticism of the gender-gender distinction, the relationships between woman-body-motherhood; and, finally, the possibilities of retaking and developing irrevocable Freudian approaches about the unconscious, the drive (Trieb) and the civilization and its discontents.